Pengaruh Pemberian Ekstrak Rumput Laut Cokelat (Sargassum duplicatum) terhadap Peningkatan Kadar Hematokrit pada Darah Tikus Putih Jantan Galur Wistar (Rattus norvegicus) Anemia yang Diinduksi NaNO2 - Emy Noviana Sandy; Liliawanti Liliawanti; Wachjudi Kurnia (Denta Journal Kedokteran Gigi, 2018)
Background: In Indonesia, the prevalence of iron deficiency anemia reaches 25,2 percent, it indicates that anemia is a medical condition in society that needs attention. Brown seaweed (Sargassum duplicatum) is a group of algae that contains minerals such as iron and vitamin B12. So that the content in Sargassum duplicatum can be used for anemia therapy that serves as the main forming hemoglobin. Objective: The purpose of this experimental research was to determine the administration of Sargassum duplicatum affects the increase in blood haemoglobin levels of rats that are anemia induced NaNO2..Methods: This research used the Post-test only control group design, the samples were 30 male rats divided into 3 treatment groups (K0, K1, and K2). The process of treating anemia in rats using sodium nitrite (NaNO2) at a dose of 125 mg / KgBB. K0 group is a group that is not treated. K1 group is a group that was given NaNO2 for 18 days without dieting Sargassum duplicatum. The K2 group was the group that was given NaNO2 for 18 days and received the Sargassum duplicatum diet at a dose of 2.45 g/kgBB for 14 days.Result: From this research it can be seen that K0 has an average hemoglobin level of 12,71 g/dL, K1 has an average hemoglobin level of 11.96 g / dL, and K2 has an average hemoglobin level of 12,99 g/dL which shows that descriptively there is a difference between groups K1 and K2. Based on the KruskalWallis statistical test, a value of 0,290 was obtained so that p > 0.05 showed that H0 was accepted, which means there was no difference in the administration of Sargassum duplicatum in increasing blood hemoglobin levels in anemic rats.Conclusion: From the results of this research, the conclusion in descriptively there was an increase in the blood hemoglobin level of white rats in the group receiving Sargassum duplicatum extract therapy but it was not statistically significant.